Implementing of Green Building Policy: From Supervision to Self-Regulatory System - Ronny Adrie Maramis; Theodorus H.W Lumunon (Hasanuddin Law Review, 2022)
The implementation of green building policies has not shown problems of effectiveness and legal level and has not gained a good momentum socially as a social movement. The introduction of policies and program implementation through the involvement of various sectors and stakeholders is necessary. General understanding of green building and its policies and enforcement is still low, but in related sectors such as civil engineering and architecture professionals as well as planning consultants have adequate knowledge. This article aims to reveal the complexity of the problems and implementation of green building in Indonesia. This study uses a normative juridical method, with a conceptual approach and field data as support. The results show that an effective way to promote, implement and monitor green building policies is to utilize a self-regulatory mechanism, a system that delegates green building regulatory to professional groups in the fields of civil engineering, architecture and contractor associations.